Community Awareness and Willingness to Participate in Electronic Waste Management: A Case Study of the District Banjarsari, Surakarta - Hashfi Hawali Abdul Matin; Timothy Jeffrey Walter Hutauruk; Ivo Solikhah; Novania Cantika Widagdo; Rony Bayu Paddy EL Maestro Setianto; Salma Ardelia Darmastuti; Thalita Aldila Pramitasari (Diponegoro University, 2021)
Hazardous and toxic waste is the residue of a business or activity containing hazardous and toxic materials which due to their nature and concentration or amount, either directly or indirectly pollute or damage and endanger the health of the environment. This study examines the awareness and willingness of the community in the management of electronic waste in Banjarsari District, Surakarta. The objectives of this study are: (i) Knowing the level of awareness of the people of Banjarsari District regarding electronic waste management; (ii) Knowing the level of willingness of the people of Banjarsari District to participate in electronic waste management; and (iii) Provide recommendations for electronic waste management in Banjarsari District. The research method uses a qualitative descriptive approach that prioritizes descriptive data, observations, and interpretations. The technique of collecting data is through primary data obtained from surveys or questionnaires to the people of Banjarsari District and secondary data derived from related literature. The results showed that the level of awareness and understanding of the electronic waste management of the people of Banjarsari District was quite good. The people of Banjarsari District have a high level of willingness to participate in waste management but are reluctant to incur additional costs due to economic and social problems. Recommendations are applied in the management in Banjarsari District by collecting, picking up electronic waste, and collaborating with third parties such as PT. Arah Environmental Indonesia.